Monitoring sterilization of dressings in high-vacuum pressure-steam sterilizers. Issue 6 (November 1961) - Fallon, R. J.
Abstract : Undetected air leaks in a high-vacuum sterilizer can defeat the sterilization process. For this reason the maintenance and supervision of these sterilizers needs expert engineering care. The importance of controlling the high-vacuum sterilization process from the centre of a load rather than the chamber drain is emphasized, and a method of detecting any failure in a high-vacuum process is described. The dynamics of the high-vacuum sterilization process are discussed and the possible disadvantages of an integrator are noted. The wisdom of using a temperature of 134°C. for three minutes is questioned.